Hyperosmolarity in children with hyperammonemia: a risk of brain herniation at the start of renal replacement therapy - Maghmoul, Yousra; Wiedemann, Arnaud; Barcat, Lucile; Parente, Fabienne; Allard, Pierre; Alvarez, Fernando; Jouvet, Philippe (Frontiers in Pediatrics, 2024)
Purpose. Renal replacement therapy (RRT) is used in hyperammonemia to reduce the concentration of ammonia in the blood. In the case of plasma hyperosmolarity, RRT can also rapidly decrease plasma osmolarity, which may increase cerebral edema in these patients and favor the occurrence of brain herniation.Methods. We conducted a retrospective clinical study in a tertiary care university-affiliated hospital. All patients admitted in a Pediatric Intensive Care Unit (PICU), less than 18 years old with ammonemia >150 µmol/L and who underwent RRT between January 2015 and June 2023 were included. We collected data on plasma osmolarity levels, osmolar gap and blood ammonia levels before and during RRT.Results. Eleven patients were included (10 with acute liver failure and 1 with a urea cycle disorders). Their mean age was 36.2 months. Before RRT, the median highest measured osmolarity was 320 (305-324) mOsm/L, whereas the median calculated osmolarity was 303 (293-314) mOsm/L, corresponding to an osmolar gap of 14 mOsm/L. Ammonia blood level over 400 µmol/L are significantly associated with higher plasma osmolarity (P-Value < 0.001).In one case, a patient had a brain herniation episode after a quick osmolar drop. This episode was reversed by the administration of hyperosmolar agents and the temporary suspension of RRT.This study highlights the hyperosmolarity and high osmolar gap that occur in children with hyperammonemia. A careful monitoring and control of plasma osmolarity evolution may alert clinician on the risk of occurrence of neurological complication such as brain herniation.